2011
DOI: 10.1271/bbb.100861
|View full text |Cite
|
Sign up to set email alerts
|

Production of Anti-Amyloid β Antibodies in Mice Fed Rice Expressing Amyloid β

Abstract: The main signs of Alzheimer's disease (AD) are cognitive impairment and senile plaques composed of amyloid beta (A) observed in patients' brains. Therefore, therapy for AD focuses on the removal of A. We developed an ''edible vaccine'' that employs intestinal immunity with little to no side effects. Rice was utilized as an edible vaccine. It expressed GFP-A42. A rice was administered orally to wild-type (WT) mice causing production of anti-A antibodies. Since A rice was mixed with the cholera toxin B subunit (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We reported previously that mice were able to produce antibodies against Aβ following oral immunization and the induction of immunotolerance to vehicle proteins. 11) Therefore, the side effects induced by oral adjuvant can be avoided for safer future vaccine therapies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We reported previously that mice were able to produce antibodies against Aβ following oral immunization and the induction of immunotolerance to vehicle proteins. 11) Therefore, the side effects induced by oral adjuvant can be avoided for safer future vaccine therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Oral vaccinations using plant-derived antigens have fewer side effects than those administered by injection. 10,11,22) In addition to the benefit of immunological safety, plant-derived vaccines are considered to be safer and cheaper than those produced from animal cells or microbes. A vaccine produced from animal cells or microbes requires refinement during the manufacturing process, because animal cells may contain viruses and prions that might infect humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, when CTB was employed as an adjuvant, additional rice seed protein antibodies were detected, indicating that this vaccine may induce food allergies. As a consequence, in order to verify the vaccine’s safety, serum IgG1 and IgG2a isotypes of anti-seed protein antibodies were examined to evaluate possible inflammatory reactions, and it was observed that Aβ fed mice generated a non-inflammatory Th2 response [ 93 ]. Nonetheless, the authors stated that the production of rice seed protein antibodies might be suppressed when immunological tolerance is induced by constant rice consumption.…”
Section: Progress On Plant-based Vaccines For Alzheimer’s Diseasementioning
confidence: 99%